2008
DOI: 10.1386/jammr.1.2.165_1
|View full text |Cite
|
Sign up to set email alerts
|

Media influence on the attitudes and knowledge of York adolescents towards Islam, Muslims, the Middle East and Arabs

Abstract: That the media is negative towards Islam, Muslims, the Middle East and Arabs was the view of the vast majority of 1,515 adolescents surveyed in York in 2004. When measured against the Attitudes towards Muslim Proximity Index (AMPI) the data showed a significant association between the media as their primary source of information and negative attitudes towards Muslims. But when measured against their level of knowledge of Islam, Muslims, the Middle East and Arabs the media had only a very slight association, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is generally observed that adolescents, oldest age cohort (Ahmed, 2012; Brockett and Baird, 2008; Christian and Lapinski, 2003) and conservatives (Field, 2007) were more likely to exhibit Islamophobia. In non-Western countries, it was found that foreign media, rather than national media, perpetuates higher negative attitudes against Muslims (Ahmed, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally observed that adolescents, oldest age cohort (Ahmed, 2012; Brockett and Baird, 2008; Christian and Lapinski, 2003) and conservatives (Field, 2007) were more likely to exhibit Islamophobia. In non-Western countries, it was found that foreign media, rather than national media, perpetuates higher negative attitudes against Muslims (Ahmed, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In non-Western countries, it was found that foreign media, rather than national media, perpetuates higher negative attitudes against Muslims (Ahmed, 2012). However, personal interaction and close association with Muslims can negate Islamophobia (Ahmed, 2012; Brockett and Baird, 2008). Rane and Abdalla (2008) found that 80% of Queenslanders did not consider Muslims to be a national threat, and more than half the respondents recognized that media representations of Muslims were stereotypical.…”
Section: Resultsmentioning
confidence: 99%
“…Building on intergroup contact theory (Allport, 1954;Pettigrew, 1998), the intergroup contact hypothesis suggests that the personal intergroup contact of majority society members with racial minority members has the potential to reduce prejudices and aversion against this outgroup (Dixon & Rosenbaum, 2004;Pettigrew & Tropp, 2006). Accordingly, it was also found that personal contact with Muslims can reduce negative attitudes towards this outgroup (Ahmed, 2012;Brockett & Baird, 2008). Considering this finding in the context of hostile media perceptions, it seems reasonable that a higher level of personal contact with outgroup members leads more strongly to the perception that media coverage is biased against this spe-cific outgroup because increased contact makes people more sympathetic.…”
Section: Literature Reviewmentioning
confidence: 99%